Ruminants - The Husbandry, Economic and Health Aspects 2018
DOI: 10.5772/intechopen.72905
|View full text |Cite
|
Sign up to set email alerts
|

Twin Calving and Its Connection to Other Economically Important Traits in Dairy Cattle

Abstract: The occurrence of twin calving in Holstein Friesian cattle is 3-5%. Reproductive problems found before and after the time of calving lead to serious economic losses. The authors' aim was to form a compilation of data regarding the cause and effects of twin calving on dairy cows by comparing the reproductive performance of cows before and after calving twins vs. single calves and also analyzing the milk production of dairy cows both before and after twin calving. Cows that would have twins became pregnant earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…After decades of little research on the economic impact of twinning, ref. [ 21 ] presented a review study, in which they concluded that twinning is a double-edged sword, because it presents some pros and many cons that cannot be easily reconciled. Economically negative factors included increased incidence of abortions, ketosis, mastitis, dystocia, lower birth weight, and stillbirths; lower fertility; increased risk of culling; and, reduced milk yield.…”
Section: Economic Impacts Of Twinningmentioning
confidence: 99%
See 1 more Smart Citation
“…After decades of little research on the economic impact of twinning, ref. [ 21 ] presented a review study, in which they concluded that twinning is a double-edged sword, because it presents some pros and many cons that cannot be easily reconciled. Economically negative factors included increased incidence of abortions, ketosis, mastitis, dystocia, lower birth weight, and stillbirths; lower fertility; increased risk of culling; and, reduced milk yield.…”
Section: Economic Impacts Of Twinningmentioning
confidence: 99%
“…Ref [ 21 ] reviewed the literature regarding the possible causes and consequences of twin calving during the gestation and in the subsequent lactation. They reported that twin pregnancies have a shorter gestation period, better reproductive performance, and shorter calving interval (desirable traits).…”
Section: Economic Models To Assess Twiningmentioning
confidence: 99%
“…Decades later, an article published in Science suggested that fraternal twin calves often have two distinct blood groups, i.e., their own and that of their twin, and this was the base conceptual foundation of acquired immunological tolerance ( Owen, 1945 ). Between 3 to 5% of all pregnancies in dairy cattle result in twins ( Gáspárdy et al, 2018 ). However, the incidence of twins in beef cattle is less frequent generally not exceeding 1% in most beef herds ( Esteves et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The events of the peripartal period require special attention in dairy cattle, since the majority of those animal health problems that may potentially reduce productive and economic performance occur during this period [7]. The prevalence of twin calving is approximately 10 %, on average, although it varies widely among dairy farms [6,12]. Twin pregnancies increase the risk of pregnancy loss, dystocia, stillbirth, calf mortality, and culling of the dam, moreover, gestation length and birth weight of the calves are reduced.…”
mentioning
confidence: 99%
“…Twin pregnancies increase the risk of pregnancy loss, dystocia, stillbirth, calf mortality, and culling of the dam, moreover, gestation length and birth weight of the calves are reduced. Freemartinism occurs in 92-98 % of those twin pregnancies, when calves from both sexes are born [6,8,12].…”
mentioning
confidence: 99%